2022
DOI: 10.5194/acp-22-6393-2022
|View full text |Cite
|
Sign up to set email alerts
|

Inverse modeling of the 2021 spring super dust storms in East Asia

Abstract: Abstract. Last spring, super dust storms reappeared in East Asia after being absent for one and a half decades. The event caused enormous losses in both Mongolia and China. Accurate simulation of such super sandstorms is valuable for the quantification of health damage, aviation risks, and profound impacts on the Earth system, but also to reveal the climatic driving force and the process of desertification. However, accurate simulation of dust life cycles is challenging, mainly due to imperfect knowledge of em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…The dust plume formed at 12:00 CST on 14 March is triggered by the strong wind associated with the movement of the convective system. These findings are consistent with the results of Jin et al (2022) using inverse modeling. They revealed that windblown dust emissions originating from both China and Mongolia contribute to the SDS events that occur in spring 2021.…”
Section: Dust Source Region and Emissionsupporting
confidence: 92%
“…The dust plume formed at 12:00 CST on 14 March is triggered by the strong wind associated with the movement of the convective system. These findings are consistent with the results of Jin et al (2022) using inverse modeling. They revealed that windblown dust emissions originating from both China and Mongolia contribute to the SDS events that occur in spring 2021.…”
Section: Dust Source Region and Emissionsupporting
confidence: 92%
“…The analysis of global dust emission using inversion model constrained by available observation data reveals that current dust models on average underestimate the Asian dust emission (Kok et al, 2021). Consistently, a recent study applying data assimilation to derive dust emission suggests > 15 million tons of dust emitted from the Chinese and Mongolian Gobi Desert during the 2021 East Asia dust storm event (Jin et al, 2022). This is much higher than that in FLEXDUST-update, MERRA-2 and CAMS-F, suggesting that the dust emission schemes used in these models may miss important processes that can invigorate extreme dust emission during the dust storm event.…”
Section: Underestimation Of Dust Emission and Concentration In Flexdu...mentioning
confidence: 52%
“…It has been found that the barer, drier and more loosened soil due to the anomalous early snow melting and a lack of precipitation in spring over the dust source region, together with the exceptionally strong Mongolian cyclone developed over the source region (i.e., central and eastern Mongolia), had triggered the emission and transport of enormous amounts of dust to East Asia during this event (Gui et al, 2022;Yin et al, 2022). The 2021 East Asia sandstorm has provided a unique testbed for dust modelling, particularly in regard to dust emission schemes which has the largest uncertainties (Jin et al, 2022;Wang et al, 2022). The ability of dust models in reproducing such extreme dust events will be critical for understanding the causes and projecting the occurrences of such extreme events in the future.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time we see rapid advances in sensor technologies and the availability of aerosol measurements from large-scale network activities that can complement the modeling activities. Those measurements are preferably used to calibrate models and to perform model error corrections through the application of data assimilation techniques (Kalnay, 2002). Examples of popular aerosol measurements used for this purpose are groundbased lidar data (Yumimoto et al, 2008), surface particular matter (PM) concentration observations (Lin et al, 2008;Jin et al, 2018Jin et al, , 2019a, polar-orbiting satellite observations (Schutgens et al, 2012;Khade et al, 2013;Yumimoto et al, 2016a;Di Tomaso et al, 2017;Jin et al, 2022) and geostationary remote sensing data (Yumimoto et al, 2016b;Jin et al, 2019bJin et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Those measurements are preferably used to calibrate models and to perform model error corrections through the application of data assimilation techniques (Kalnay, 2002). Examples of popular aerosol measurements used for this purpose are groundbased lidar data (Yumimoto et al, 2008), surface particular matter (PM) concentration observations (Lin et al, 2008;Jin et al, 2018Jin et al, , 2019a, polar-orbiting satellite observations (Schutgens et al, 2012;Khade et al, 2013;Yumimoto et al, 2016a;Di Tomaso et al, 2017;Jin et al, 2022) and geostationary remote sensing data (Yumimoto et al, 2016b;Jin et al, 2019bJin et al, , 2020. Among available measurements, satellite aerosol products provide valuable information through their high spatial coverage: a single instrument is used to observe a large spatial area making additional harmonization efforts unnecessary.…”
Section: Introductionmentioning
confidence: 99%